Heterotic gains, transgressive segregation and fitness cost of sweetpotato weevil resistance expression in a partial diallel cross of sweetpotato - Mugisa, I.; Karungi, J.; Musana, P.; Odama, R.; Anyanga, M.O.; Edema, R.; Gibson, P.; Ssali, R.T.; Campos, Hugo; Oloka, B.; Yencho, George Craig; Yada, B. (Springer, 2023)
Heterosis-exploiting breeding schemes are currently under consideration as a means of accelerating genetic gains in sweetpotato (Ipomoea batatas) breeding. This study was aimed at establishing heterotic gains, fitness costs and transgressive segregation associated with sweetpotato weevil (SPW) resistance in a partial diallel cross of sweetpotato. A total of 1896 clones were tested at two sites, for two seasons each in Uganda. Data on weevil severity (WED), weevil incidence (WI), storage root yield (SRY) and dry matter content (DM) were obtained. Best linear unbiased predictors (BLUPs) for each clone across environments were used to estimate heterotic gains and for regression analyses to establish relationships between key traits. In general, low mid-parent heterotic gains were detected with the highest favorable levels recorded for SRY (14.7%) and WED (− 7.9%). About 25% of the crosses exhibited desirable and significant mid-parent heterosis for weevil resistance. Over 16% of the clones displayed superior transgressive segregation, with the highest percentages recorded for SRY (21%) and WED (18%). A yield penalty of 10% was observed to be associated with SPW resistance whereas no decline in DM was detected in relation to the same. Chances of improving sweetpotato through exploiting heterosis in controlled crosses using parents of mostly similar background are somewhat minimal, as revealed by the low heterotic gains. The yield penalty detected due to SPW resistance suggests that a trade-off may be necessary between maximizing yields and developing weevil-resistant cultivars if the current needs for this crop are to be met in weevil-prone areas.